Anglicizmi u švedskom - neki aspekti fonološke i morfološke adaptacije - Antunović, Goranka (Array, 1988)
Following a brief presentation of the corpus of loan words included in the dictionary 'Nyord i svenskan fraan 40-tal till 80-tal', the article focuses on adaptation of anglicisms in Swedish. The written form of anglicisms is discussed first, according to the principles described in Filipović 1986, and some conspicuous phenomena in the process are pointed out. Some possibilities regarding the phonological adaptation of anglicisms are discussed next, on the basis of the pronunciation notes given in the dictionary. The appropriateness of the "engl. uttal" (=Eng. pronunciation) note is commented upon, and some examples of free transphonemization are cited. The last section deals with the morphological adaptation of English loan-nouns in Swedish, notably with gender assignment and creation of plural forms.